Biomass valorization by thermal treatments: Graphene-based materials and their application on glyphosate adsorption - Hernández-Barreto, Diego Felipe; Bernal, Valentina; Giraldo, Liliana; Moreno-Piraján, Juan Carlos; Rodriguez-Estupiñán, Paola (Frontiers in Sustainability, 2022)
Carbon-based nanomaterials have exceptional physicochemical properties like high surface area and active sites, suitable for the adsorption of inorganic and organic compounds. Currently, these materials are being tested for environmental applications, e.g., detecting emerging pollutants in drinking and surface water. This work reviews different methods to prepare graphene (G) or graphene-based materials (GBM) using biomass or its constituents. This text brings together the methods used to revalue biomass by converting it into graphene materials from thermal treatments and their application in the adsorption of glyphosate from an aqueous solution. Computational studies were also added to evaluate the information about interactions between the herbicide and graphene layers.